La Facultad de Ciencias de la Educación y sus 50 años de funcionamiento - Campos Arenas, Agustín (2012)
A historical overview of Education School throughthe 50 years of operation is presented. Importantdates and legal norms associated with the academicprograms of the School and authorities that hadthe responsibility to practice the School charges.Significant achievements occurred during these 50years are reported.